Initial effects of fertilization and canopy management on flowering and seed and oil yields of Jatropha curcas L. in Malawi - Negussie, A.; Achten, W.M.J.; Norgrove, L.; Mekuria, Wolde; Hadgu, K.M.; Both, G. de; Leroy, B.; Hermy, M.; Muys, B. (Springer, 2016)
Appropriate canopy management, including planting density and pruning, and application of fertilizer may increase flowering success and seed and oil yields of Jatropha curcasL.Twofieldexperimentswereperformedfrom2009to 2011 in Balaka, Malawi, to assess the effect of planting density and pruning regime and single fertilizer application (N, P, and K) on male and female flower number and seed and oil yields of J. curcas. Planting density influenced flower sex ratio and female flower number. Branch pruning treatments did not influence the flower sex ratio but reduced seed and final oil yield by 55 % in the following year. It is claimed that J.curcas can be grown on soils with low nutrient content, but this study revealed that yield was low for non-fertilized trees. WeobservedhigherseedandoilyieldsathigherNapplication rates(upto203±42%seedand204±45%oilyieldincrease) compared with the non-fertilized control. The study suggests thatcurrentlyusedheavypruningpracticeisnotrecommended for J.curcas cultivation, although it needs further longer term investigation. Applying nitrogen fertilizer is effective in increasing yield.